2022
DOI: 10.1007/s00167-022-06865-z
|View full text |Cite
|
Sign up to set email alerts
|

Complications after high tibial osteotomy and distal femoral osteotomy are associated with increasing medical comorbidities and tobacco use

Abstract: Purpose The purpose of this study was to assess complications, reoperations, and their risk factors at 90 days and 2 years after high tibial osteotomy (HTO) and distal femoral osteotomy (DFO) in a national cohort. Methods The PearlDiver Mariner Dataset was queried using International Classiication of Diseases (ICD) and Current Procedural Terminology (CPT) codes for HTO and DFO, complications, and subsequent surgery. Minimum follow-up was 2 years and complications were assessed at 90 days and 2 years. Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A 2022 retrospective review of the Pearl-Diver Mariner data set reported a 90-day complication rate of 11.6% after HTO and 21.5% after DFO among a total of 2226 patients (1780 HTO, 446 DFO). 20 The most common complications after both HTO and DFO were infection (3.9% HTO, 6.1% DFO), hardware-related complications (2.8% HTO, 4.9% DFO), and wound disruption (1.8% HTO, 2.7% DFO). In a 2020 retrospective review of the American College of Surgeons National Surgical Quality Improvement Program, Cotter et al 11 reported complication rates of 22.3% among patients undergoing DFO and 9.9% among patients undergoing HTO.…”
Section: Surgical Details and Concomitant Proceduresmentioning
confidence: 97%
“…A 2022 retrospective review of the Pearl-Diver Mariner data set reported a 90-day complication rate of 11.6% after HTO and 21.5% after DFO among a total of 2226 patients (1780 HTO, 446 DFO). 20 The most common complications after both HTO and DFO were infection (3.9% HTO, 6.1% DFO), hardware-related complications (2.8% HTO, 4.9% DFO), and wound disruption (1.8% HTO, 2.7% DFO). In a 2020 retrospective review of the American College of Surgeons National Surgical Quality Improvement Program, Cotter et al 11 reported complication rates of 22.3% among patients undergoing DFO and 9.9% among patients undergoing HTO.…”
Section: Surgical Details and Concomitant Proceduresmentioning
confidence: 97%
“…However, for patients with limited bone metabolism such as elderly patients, smokers, patients with diabetes or poor bone quality, according to the results of Ziegler et al , a supportive therapy for ossification can be justified ( 51 ). Especially since increased complication rates have been described for these patient groups ( 54 , 55 , 56 ). This is also conceivable in the case of postoperatively proven hinge fractures with higher rates of pseudarthrosis ( 57 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
“… 6 , 7 One of the most common complications of a distal femoral osteotomy is symptomatic hardware. 5 , 8 , 9 The authors aim to limit this complication by their plate-positioning tips. By initially placing the plate flush on the bone distally, the planned osteotomy correction typically allows for the plate to sit flush on the bone proximally at the end of the procedure.…”
Section: Discussionmentioning
confidence: 99%